Funny people [videorecording (DVD)] - Apatow, Judd, 1967-; Sandler, Adam; Rogen, Seth, 1982-; Mann, Leslie, 1972-; Bana, Eric; Hill, Jonah, 1983-; Schwartzman, Jason, 1980-; Kamiński, Janusz, 1959-; Schwartzman, Jason, 1980-; Andrews, Michael, 1967- (Universal Studios Home Entertainment, 2009)
George is a very successful stand-up comedian who learns that he has less than a year to live. Ira, who is a struggling up-and-coming comedian works at a deli. One night the two perform at the same club, and George decides to make Ira his best friend. This lopsided relationship gradually takes on aspects of true friendship as Ira forces George to try to reconnect with the people in his life, including his ex-girlfriend Laura.